IDDF2020-ABS-0150 Adherence to Best Practices in the Detection and Characterisation of Premalignant Upper Gastrointestinal Lesions among Endoscopists in India: A Survey. (18th November 2020) - Madhu, Deepak; Krishnamurthy, Veeraraghavan; Natarajan, Thirumoorthi; Lakhtakia, Sundeep
Abstract : Background: Given the high morbidity of gastric and esophageal cancers and the absence of population-based screening in India, it is important that all elective Esophago-Gastro-Duodenoscopies (EGDs), irrespective of the primary indication, be viewed as an opportunity to screen for pre-malignant lesions as this will help in early detection of these cancers. With this premise, we aimed to assess the adherence to best practices with regard to the detection of pre-malignant upper gastro-intestinal lesions (PMUGIL) among endoscopists in India. Methods: We conducted an electronic survey among endoscopists in India with the primary objective of assessing adherence to best practices (an arbitrary threshold of 90% adherence was considered adequate) and with the secondary objectives of assessing the adequacy of training, availability of appropriate facilities and differences between teaching and non-teaching centers. Results: Among 422 eligible responses, the adherence to best practices assessed were lower than the set threshold in all except one metric (table 1 ) in both teaching centers and non-teaching centers. Only 58.5% of endoscopists had received training in the detection of PMUGIL. Appropriate Image Enhanced Endoscopy (IEE) facilities for evaluating PMUGIL were available to only 58.05% of surveyed endoscopists. Conclusions: Strategies to improve detection of PMUGIL should be directed at improving best practice adherence, training and endoscopy equipment.